Mencetak Generasi yang Berakhlak Mulia: Perspektif Pendidikan dalam Tafsir al-Mishbah dan Tafsir al-Azhar pada Q.S. As-Saffat Ayat 100-111 - Maulidia Maulidia; Taufik Warman Mahfuzh; Zainap Hartati (Syams, 2021)
Al-Qur’an Surah As-Saffat Verse 100-111 shows that Islamic teachings are very concerned about how important it is to create a generation that has noble character and is close to their Lord. This illustrates that the content of the verse has an educational perspective. However, in order not to leave the spirits of Islamic education, it is necessary to put the thoughts of the scholars into one of their works, including the interpretation of the Qur’an. This article concludes: First, the educational perspectives contained in the interpretation of al-Mishbah are: 1) Religious values, namely belief in God, divine guidance, trials, tawakkal, patience, piety, and the fruit of faith; 2) Social values, namely honest, democratic, and polite; 3) Ethical values, namely responsibility, hard work, and resilience; and 4) Aesthetic Values, namely appreciating achievements, giving values and awards. Second, the educational perspective contained in the interpretation of al-Azhar are: 1) Religious values, namely belief in God, divine guidance, trials, patience, tawakkal, syaja’ah (courage) and piety; 2) Ethical values, namely hard work, the fruit of faith; and 3) Aesthetic Values, namely appreciating achievements and giving values and awards. Third, the educational perspective contained in the two interpretations is understood from almost the same substance, the difference only lies in the narrative.